PERAN GURU AKIDAH AKHLAK DALAM MEMBENTUK MOTIVASI BERPRESTASI SISWA KELAS VIII DI MTS ALWASHLIYAH SELAT BESAR LABUHANBATU - Asrani Lubis; Pan Su’aidi; Yulia Warda (Journal of Innovative and Creativity, 2026)
The purpose of this study is to describe and analyze the strategic role of Akidah Akhlak teachers in fostering achievement motivation among grade VIII students at MTs Alwashliyah Selat Besar, Labuhanbatu. This research employs a qualitative descriptive approach with a field research design. Data were collected through in-depth interviews, participant observation, and documentation studies. The primary informants included Akidah Akhlak teachers and grade VIII students, selected through purposive sampling. Data analysis followed the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing, with triangulation used to ensure data validity. The findings indicate that Akidah Akhlak teachers play a multifaceted role as motivators, role models (uswah hasanah), and counselors. Teachers internalize the value of fastabiqul khairat (competing in goodness) and the doctrine of "Man Jadda Wajada" to transform students' mindsets toward academic success. Strategies used include positive reinforcement through rewards, the use of inspirational stories of Islamic figures, and the creation of a competitive classroom climate. Although hindered by challenges such as a lack of parental supervision at home and limited technological facilities, the teacher's role has significantly improved students' learning discipline and participation. The study concludes that the integration of spiritual values and persuasive pedagogical approaches is effective in building a strong achievement mentality in students.